2020
DOI: 10.1136/bmjgh-2019-002166
|View full text |Cite
|
Sign up to set email alerts
|

Building HIV healthcare worker capacity through telehealth in Vietnam

Abstract: Development of a robust technical assistance system is an essential component of a sustainable HIV response. Vietnam’s National HIV Program is transitioning from a largely donor-funded programme to one primarily supported by domestic resources. Telehealth interventions are increasingly being used for training, mentoring and expert consultation in high-resource settings and hold significant potential for use as a tool to build HIV health worker capacity in low and middle-income countries. We designed, implement… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(35 citation statements)
references
References 31 publications
0
23
0
Order By: Relevance
“…Among the included articles, sub-Saharan Africa (28/31, 90%) was the most represented geographical region [ 1 , 8 , 15 - 17 , 30 - 52 ]. Countries in Southeast Asia were represented in 10% (3/31) of the studies [ 45 , 53 , 54 ], and 3% (1/31) of the studies included participants across Africa, Asia, and South America [ 1 ]. A wide array of health care cadres was targeted across the studies, including nurses, physicians, midwives, community health workers, public health specialists, hospital administrators, and health officers.…”
Section: Resultsmentioning
confidence: 99%
“…Among the included articles, sub-Saharan Africa (28/31, 90%) was the most represented geographical region [ 1 , 8 , 15 - 17 , 30 - 52 ]. Countries in Southeast Asia were represented in 10% (3/31) of the studies [ 45 , 53 , 54 ], and 3% (1/31) of the studies included participants across Africa, Asia, and South America [ 1 ]. A wide array of health care cadres was targeted across the studies, including nurses, physicians, midwives, community health workers, public health specialists, hospital administrators, and health officers.…”
Section: Resultsmentioning
confidence: 99%
“…Besides, healthcare providers must comply with the policy of MOH about participating in continuing education with at least 48-h within 2 years to maintain their work permit certificates. In fact, the continuous learning applied the ECHO model had improved the capacity of HIV healthcare workers in Vietnam a great deal that 90% of participants wanted to participate in the next courses [ 7 ]. Another study also indicated that the pediatric care providers improved their professional knowledge and skill after following Project ECHO training [ 15 , 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…Thus, as the Project ECHO has to run by its resource in the future, it is essential to examine the factors that impact the program’s sustainability. Although previous studies have mentioned the feasibility and acceptability of Project ECHO [ 6 , 14 , 15 , 20 ], few researchers have studied the sustainability of the program [ 7 , 39 ]. To ensure the sustainability of Project ECHO, the financial issue is crucial because the project has to invest in human resources, devices and the online network [ 39 , 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, a number of projects have initiated and implemented digital health services in large urban hospitals, including teleradiology, teleconsultation, telediagnosis, and videoconferencing. Examples of these initiatives include raising disease awareness and encouraging people to adopt heathier behaviors [65][66][67][68][69], improving accessibility to health care services among disadvantaged and vulnerable target groups [70][71][72], and upskilling health care workers [73][74][75][76][77][78][79][80].…”
Section: Opportunitiesmentioning
confidence: 99%